Generating Ectropis obliqua axenic larvae in support of functional microbiome studies. Issue 10 (16th August 2022) - Su, Qingqing; Zhao, Yu; Zhou, Linlin; Li, Xiayu; Wu, Zhenzhen; Zhang, Yong; Yang, Yunqiu; Long, Yanhua
Abstract: Ectropis obliqua Prout (Lepidoptera: Geometridae) is a serious leaf‐eating pest in tea gardens throughout China, with rich bacterial communities in the larval gut. Few studies have investigated whether these bacteria play an important role in growth, development, and adaptability of E. obliqua . Axenic larval models are a useful tool for the study of interactions between gut bacteria and host insects. At present, artificial diet and antibiotics are typically used to remove larval gut bacteria for study; however, this method may change the natural food of insects and the habitat provided by their host plants, and cannot completely eliminate insect gut bacteria. Therefore, in order to establish an axenic insect feeding model, we first investigated the effects of egg age, different disinfectant concentration, and treatment time on the eggs of E. obliqua through orthogonal experiments. Next, we fed E. obliqua larvae tissue‐cultured tea seedlings under aseptic conditions. Thus, we successfully generated a feeding model of gut axenic larvae in the laboratory. Based on it, we then compared the mortality of axenic and non‐axenic E. obliqua larvae infected with the entomopathogenic fungus Beauveria bassiana (Balsamo) Vuill. These results demonstrated the feasibility of this axenic larval model and that B. bassiana is a broad‐spectrum entomogenous fungus with a toxic effect on E. obliqua . Abstract : We investigate the effects of egg age, disinfectant concentration, and treatment time on fertilized eggs of Ectropis obliqua (Lepidoptera: Geometridae) by orthogonal experiments, combining sterile tea seedlings obtained by culture technology, establishing a stable axenic E. obliqua feeding system in laboratory, without administering antibiotics or artificial diet. We also compare the mortality of axenic and non‐axenic E. obliqua larvae infected with entomopathogenic Beauveria bassiana . This model would help understand the role of gut microbiota in many insect physiological functions.